2007
DOI: 10.1007/bf02912875
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction—Homocysteine in Coronary Heart Disease

Abstract: Majority of patients who experience a Coronary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…It also turned out to be the one with the highest specificity and accuracy among all the risk factors compared. The results were consistent with other studies [15,16]. However, the levels of folate and other vitamins were not included in the study; it can, therefore, be a limitation in concluding the hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…It also turned out to be the one with the highest specificity and accuracy among all the risk factors compared. The results were consistent with other studies [15,16]. However, the levels of folate and other vitamins were not included in the study; it can, therefore, be a limitation in concluding the hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…To determine the linkage between homocysteine and atherosclerosis, various theories has been established, ideas like Growth stimulation of smooth muscles, reduced growth of the endothelial cells, loosening of endothelial cells and dropping in the High DL production [10; 6]. Our data results are in a accordance with previous works done by many researchers from different countries showing a significant raised total serum homocysteine level in ischemic heart disease (unstable angina) [16][17][18][19][20][21][22] .It might be due to deficiency of vitamins B6, B12 and folic acid deficiency. Previous works also explained that homocysteine compound undergoes metabolism by transsulfuration and remethylation pathway.…”
Section: Serum Mda Levels Of the Study Populationsupporting
confidence: 90%
“…Twenty CVD conditions (71.4%) of the twenty four studies found that plasma tHcy levels can be employed as a biomarker for the risk of CVD [22,24,25,29,42,43,46,48,[52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%